PENGARUH PEMBERIAN BUAH NAGA (Hylocerreus polyrhizus) TERHADAP PENINGKATKAN KADAR HEMOGLOBIN PADA IBU HAMIL DI PUSKESMAS NARAS - RISHEL, RIKA ASTRIA; PRASETYANINGSIH, PRASETYANINGSIH; ZANAH, MIFTAKHUL; SHALIHAH, SRI RIZKI (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Anemia in pregnancy is a problem that requires special treatment because its prevalence is still high. According to WHO 2017, anemia in pregnancy is a condition in which a mother has a hemoglobin level of <11 gr% in the first and third trimesters, while in the second trimester the hemoglobin level of pregnant women is <10.5 gr. The purpose of the study was to determine the effect of giving dragon fruit (hylocerreus polyrhizus) on increasing hemoglobin levels in pregnant women in the Naras Health Center Work Area. This type of research uses an experimental method with a one group pre-test and post-test design. The sample in the study was 15 pregnant women who had anemia. Statistical tests using the Paired Sample Test. The results of the study were obtained before giving dragon fruit to pregnant women in the Naras Health Center Work Area, Pariaman City 2023 with a moderate anemia category, namely 8 respondents (53.0%). After giving dragon fruit with a mild anemia category, namely 11 respondents (73.3%). In conclusion, there is a significant effect on increasing hemoglobin (HB) levels in pregnant women with anemia after being given dragon fruit in the Naras Health Center work area, Pariaman City, with a P value of 0.001 (p<0.05).